Status of Franchisor-Franchisee Relationship (SFFR) on Business Performance of Tata Ilio: Basis for Sustainability: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The purpose of this study is to determine the status of the franchisor-franchisee relationship(SFFR) on the business performance of Tata Ilio: the basis for sustainability in terms of trust,satisfaction, commitment, financial performance, relationship performance, and service.From the results of this study. It reveals that the franchisor-franchisee relationship on TataIlio's sustainability is evaluated as "always sustainable" in terms of trust, satisfaction, andcommitment. It also reveals that in the franchisor-franchisee relationship in the businessperformance of Tata Ilio, the overall performance is evaluated as "good performance" in termsof finances, relationships, and service. The conflicts encountered in terms of the franchisor-franchisee relationship, the poor communication in business changes, and misunderstandingin cost and royalty add up to the highest main conflicts of Tata Ilio in terms of the franchisor-franchisee relationship there. Can an action plan be proposed to sustain the franchisor-franchisee relationship of business performance in Tata Ilio?This study recommended that the Tata Ilio franchise should continue to maintain the businessperformance at its high franchise rate and be consistently transparent, committed, and fair forthe continuing sustaining the business performance and relationship of franchisor-franchisee.
Keywords: Business